The role of competitive fluid-rock interaction processes in the formation of high-grade gold deposits. (15th November 2021) - Petrella, Laura; Thébaud, Nicolas; Evans, Katy; LaFlamme, Crystal; Occhipinti, Sandra
Abstract: Although forming one unified class, orogenic gold deposits may be associated with a range of ore mineral assemblages controlled by a variety of gold deposition processes that have a direct impact on gold grade. Whereas, a better understanding of the deposition process may be critical for effective targeting of highly-endowed gold deposits, it is challenging to establish a direct comparison between mineral systems formed under different conditions. Accordingly our ability to predict whether contrasted mineral associations may be more or less prospective for high grade mineralization remains poor. In this paper, we compare fluid-rock interaction processes that led to the coeval formation of two contrasting gold mineral assemblages within the world-class Callie orogenic gold deposit. Stratabound and vein-hosted lodes formed within the same structural framework but with contrasting grades (∼3 g/t Au and ∼8 g/t Au, respectively). The stratabound mineralization consists of bedding-parallel sulfides in which gold is preserved in arsenopyrite micro-fractures. The vein-hosted mineralization consists of locally very high-grade (up to 10, 000 ppm Au) visible gold concentrated in quartz veins. Both mineralization styles are hosted within different metasedimentary stratigraphic horizons with contrasting compositions. The stratabound mineralization occurs in iron-oxide rich siltstones whereas the vein-hosted mineralization occurs in carbonaceous siltstones. We investigate the fluid-rock interaction mechanisms of the two styles of mineralization at the Callie deposit by combining petrographic observation with whole-rock geochemistry, quantitative chlorite and gold analyses and thermodynamic modeling. Our results show that the stratabound mineralization occurred in response to sulfidation of the host-rock whereas decarbonation alteration, associated with the vein-hosted mineralization, records oxidation of the host-rock. Our investigation shows that gold deposition induced by oxidation of the host-rock produces the valuable, locally very-high grade visible gold mineralization whereas the sulfidation process lead to the formation of lower grade gold mineralization disseminated within the sulphide ore assemblage. We conclude that the nature of the host-rock applies a first-order control on the gold deposition efficiency in metasedimentary-hosted gold deposits.